2014
DOI: 10.1093/hmg/ddu276
|View full text |Cite
|
Sign up to set email alerts
|

Rare and common variants in extracellular matrix gene Fibrillin 2 (FBN2) are associated with macular degeneration

Abstract: Neurodegenerative diseases affecting the macula constitute a major cause of incurable vision loss and exhibit considerable clinical and genetic heterogeneity, from early-onset monogenic disease to multifactorial late-onset age-related macular degeneration (AMD). As part of our continued efforts to define genetic causes of macular degeneration, we performed whole exome sequencing in four individuals of a two-generation family with autosomal dominant maculopathy and identified a rare variant p.Glu1144Lys in Fibr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 63 publications
2
41
0
1
Order By: Relevance
“…New genetic variants were detected in CFH , CFI , C3 and C9 , in addition to other genes ( FBN2 and HMCN1 ). Although rare variants segregated with AMD in some of these families (Pras et al, 2015, Ratnapriya et al, 2014, Yu et al, 2014), several variants did not perfectly segregate with the disease, but were enriched in cases compared to control individuals (Geerlings et al, 2016, Hoffman et al, 2014, Saksens et al, 2016). This is in line with the complex etiology of AMD, to which both common and rare genetic variants, and also environmental factors contribute.…”
Section: The Complement System Plays a Central Role In The Etiology Omentioning
confidence: 92%
See 1 more Smart Citation
“…New genetic variants were detected in CFH , CFI , C3 and C9 , in addition to other genes ( FBN2 and HMCN1 ). Although rare variants segregated with AMD in some of these families (Pras et al, 2015, Ratnapriya et al, 2014, Yu et al, 2014), several variants did not perfectly segregate with the disease, but were enriched in cases compared to control individuals (Geerlings et al, 2016, Hoffman et al, 2014, Saksens et al, 2016). This is in line with the complex etiology of AMD, to which both common and rare genetic variants, and also environmental factors contribute.…”
Section: The Complement System Plays a Central Role In The Etiology Omentioning
confidence: 92%
“…Since WES and WGS are expensive to perform in large cohorts, approaches can be used to enrich for rare variants, for example by analyzing large AMD families. Recent studies in AMD using WES and WGS have successfully identified novel genetic variants in AMD using a case-control cohort (Helgason et al, 2013) or by analyzing multiple affected individuals of large AMD families (Duvvari et al, 2016, Geerlings et al, 2016, Hoffman et al, 2014, Pras et al, 2015, Ratnapriya et al, 2014, Saksens et al, 2016, Yu et al, 2014). New genetic variants were detected in CFH , CFI , C3 and C9 , in addition to other genes ( FBN2 and HMCN1 ).…”
Section: The Complement System Plays a Central Role In The Etiology Omentioning
confidence: 99%
“…It is likely that some combination of those different potential mechanisms accounts for the underlying architecture of complex diseases and traits as common, low frequency, and rare variants have all now been shown to be associated with complex diseases and traits Morrison et al 2013;Ratnapriya et al 2014;Surakka et al 2015).…”
Section: The Landscape Of Genetic Association Signalsmentioning
confidence: 99%
“…Recent studies where whole exome/genome sequencing strategies were used have resulted in the successful identification of several rare variants, including the p.K155Q variant in C3 ,28 p.E1144 K variant in FBN2 29 and three other CFH variants: p.P503A,30 p.R53C and p.D90G 31. Another, yet to be implicated, benefit of this application relates to the comprehensive genetic data provided on multiple common and rare variants collectively, which could shed better insights into genotype–phenotype correlations.…”
Section: Introductionmentioning
confidence: 99%